Photocatalytic Degradation of Paraquat Dichloride using TiO2-Fe Nano Powder under Visible and Sunlight Irradiation - Linda J Kusumawardani; Yulian Syahputri; Ani Iryani (Syarif Hidayatullah State Islamic University, 2020)
Paraquat dichloride, is an active herbicide with the chemical formula [(C6H7N2)]Cl2, and in the last decade became the most widely used agricultural pesticide in Indonesia. It has an important role in oil palm plantations but recently appeared many problems and caused environmental pollution. In this research, the photodegradation of paraquat herbicide using TiO2-Fe nanopowder was investigated. The TiO2-Fe catalyst was prepared by the sol-gel method and characterized using XRD and DRS. The characterization results showed that Fe as a dopant on TiO2 produced a small crystal size. This condition can increase the performance of photocatalysis from the area of UV to visible light. Degradation of paraquat dichloride is carried out under visible and sunlight irradiation to significantly increase photocatalytic activity. Decreasing of paraquat content was observed for every 15 minutes and measured by spectrophotometer UV-Vis. The addition of 0.5 gram of TiO2-Fe catalyst to 50 mL of sample solution increased the degradation percent by 98.4% for 75 minutes with a concentration of Fe3+ 10% (w/w). These results indicate that the presence of Fe dopants on TiO2 can increase the photocatalytic activity of nano TiO2 particles from UV light to visible light.